Lectura, literatura y justicia en la formación académica - Vila, Rosa (2013)
"Work developed within the context of the Readers for Justice Project, accredited by the University of Buenos Aires Science and Technology (UBACYT) Program 2012-2014." -- In this paper we investigate possible relationships between the concepts of "Reading", "Literature" and "Justice", as the starting point for the project called "Readers for Justice". This project promotes silent and loud voice reading practices at the University, and from the University to the community, involving the educational value of reading in the most varied instances of life, including all levels of Education. Furthermore, it is built on the idea that Literature can act as a bridge between reality and the most diverse disciplines.